Improved irrigation water management- a direct benefit of a water conservation program - Dimmitt, Arnold K., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
Implementation of the 15 projects in the Water Conservation Program (program) identified in the landmark December 1988 Water Conservation Agreement (Agreement) between Metropolitan Water District of Southern California (Metropolitan) and Imperial Irrigation District (Imperial) and in the December 1989 Approval Agreement among Metropolitan, Imperial, Palo Verde Irrigation District, and Coachella Valley Water District began in January 1990. The last major construction work was completed in December 1997. While the Program has focused primarily on modernizing and rehabilitating Imperial's irrigation distribution system, it has included on-farm water management projects that permit greater water management flexibility for the farmers and opportunities for farmers to apply water more effectively. In actuality, both distribution system and on-farm management improvements are, in some cases, interrelated such that one without the other would reduce the effectiveness of any individual project, of the Program, by itself. The level of the Program's effectiveness has been demonstrated through a process of verifying each project's accomplishments. This paper will review the various projects completed to improve Imperial's overall irrigation system and use of water and how the projects were planned, managed, and the conserved water verified. Additionally, an update on the Program's costs and resulting conserved water volume will be presented.
USCID 14th technical conference
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.